Analysis of Total Quality Management Implementation At Hemra Hotel Balikpapan - Iliana Savana Fasya; Baroya Mila Shanty; Kenny Roz (Universitas Muhammadiyah Malang, 2022)
This research was conducted at Hemra Hotel Balikpapan. The purpose of this study is to find out how the views of employees and consumers on the implementation of TQM and to find out whether there is a difference between the views of employees and consumers regarding the implementation of TQM at Hemra Hotel. The data analysis technique used is the Scale Range and Difference Test with the calculation process using SPSS. the views between employees and consumers on the implementation of TQ M at Hemra Hotel are that there are three dimensions that are stated to be significant, namely, customer focus, obsession with quality, employee empowerment, which means that there are differences in views between employees and consumers. Meanwhile, the other seven dimensions, namely scientific approach, long-term commitment, teamwork, continuous improvement, education and training, freedom of control, and unity of purpose were stated to be insignificant, which means there is no difference between employees and consumers. Suggestions for this research are to increase the variables that are still considered lacking, namely, focus on customers, obsession with quality, and employee empowerment.